Our Relationship with "Authority" − Political, Religious and Ecclesiastical - Nikolchev, Dilyan (Forum Theologicum Sardicense, 2025)
Dilyan Nikolchev, Our Relationship with "Authority" − Political, Religious and Ecclesiastical. The current paper analyzes key aspects of the modern crisis regarding the concept of authority. It addresses the social and moral issues facing contemporary society and highlights the significant challenges that Church practice encounters today in Bulgaria.